Supplementation of Parachlorella sp. in feed promote the gut microbiome colonization and fecal IgA response of broiler in both early and late period - Woonhak Ji; Tae-Yong Kim; Chae Won Lee; Z-Hun Kim; Ji Young Jung; Byeong Cheol Ban; Changsu Kong; Myunghoo Kim (Poultry Science)
This study evaluated the effects of Parachlorella sp. KSN1 (PA) supplementation on the gut microbiota and intestinal immunity of broilers of different ages. A total of 180 Ross 308 broiler chicks were weighed and divided into early (1 to 10 days post hatch) and late (11 to 28 days post hatch) periods, with six replicates of 10 chicks per cage assigned to two dietary groups. The experimental diets included a corn-soybean meal-based control diet and a treatment diet supplemented with 0.5% PA, replacing corn or corn starch, and fed ad libitum for the assigned experimental period. On days 10 and 28, two broilers from each of the six replicate cages, with 7 broilers per cage in each group, were selected and euthanized, and cecal feces and intestinal tissue samples were collected. PA supplementation did not significantly affect broilers growth performance during both the early and the late periods. However, PA supplementation altered the cecal microbiome, with Clostridiaceae and Clostridium exhibiting prominent and consistent changes. In terms of intestinal immunity, PA supplementation significantly increased the number of CD3+ and CD4+ T cells when administered only during the early period. Cecal IgA levels were significantly increased by PA supplementation during both the early and late periods. A significant positive correlation was observed between IgA, Clostridiaceae and Clostridium during the early and late periods. Gene expression analysis identified 40 upregulated genes, including polymeric immunoglobulin receptor (pIgR), and 142 downregulated genes, including marginal zone B and B1 cell specific protein and immunoglobulin lambda-like polypeptide 1 that were associated with the IgA response in PA-treated broilers during the early period. This study demonstrated that PA supplementation promotes gut microbial colonization and intestinal immunity development during the early age of broilers. These findings suggest that the early growth period of broilers is the optimal time for dietary immunomodulation to promote gut health in broilers.